A study of the effects of 8-week acupuncture treatment on patients with Parkinson's disease - Yeo, Sujung (Medicine (Baltimore), 2018)
BACKGROUND: Parkinson's disease (PD) is a degenerative brain disorder, resulting in decreased neural responses in the supplementary motor area, putamen, and thalamus. Previous research showed that acupuncture was able to improve the motor dysfunction. The primary aim of this study is to assess the efficacy of longer acupuncture treatment for preventing brain degeneration in patients with PD. METHODS: Ten outpatients with PD were recruited from Kyung Hee Medical Hospital. Behavioral and neural responses were examined before and after 8 weeks of acupuncture treatment. A semi-individualized treatment approach was used; patients were treated for 15 minutes with 120-Hz electro-acupuncture at the right GB34 and Taechung (LR3), followed by manual acupuncture based on the individual symptoms of the patient. RESULTS: Immediately after 8 weeks of acupuncture treatment, the Unified Parkinson's Disease Rating Scale (UPDRS) sub-scores and the depression scores for the patients had statistically decreased compared to the scores before acupuncture treatment; moreover, 8 weeks later, these scores remained stable. Compared to the neural responses before the acupuncture stimulation, those after the acupuncture treatment were significantly higher in the thalamus, cingulate gyrus, anterior cingulate, lingual gyrus, parahippocampal gyrus, lateral globus pallidus, mammillary body, middle temporal gyrus, cuneus, and fusiform gyrus. Finally, a positive correlation was found between the UPDRS and the mean magnetic resonance signal change for the thalamus. CONCLUSION: This study found beneficial clinical effects of 8-week acupuncture treatment in the brains of patients with PD.